Through Area-Wide Farmers’ Participatory Approach... Managing coconut rhinoceros beetle - Anithakumari, P; Mohan, Chandrika; Krishnakumar, V; Muralidharan, K; Chowdappa, P (Indian Horticulture, 2019)
The Oryctes rhinoceros (L.), popularly known as black beetle, is major pest of coconut in all coconut-growing states. This pest affects different stages of growth, viz. coconut seedlings, juveniles and adult bearing palms. Severe infestation of young plants leads to reduction in growth, sometimes, even loss of plants in the field. It can also induce considerable yield reduction by the damage inflicted in unopened bunches in bearing palms. The typical symptoms are geometrical Vshaped cuttings in opened coconut fronds. In some cases, toppling of spindle leaves also can be noticed. In many coconut gardens, 25-40 per cent of total palms could be found to be showing rhinoceros beetle infestation symptoms. Hence, the yield reduction is considerable in a given area, which warrants adoption of management technologies. Attack by the beetle could act as a predisposing factor for subsequent attack of red palm weevil and complete death of palm. Though many management practices including biocontrol approaches are recommended, there is only very low level of awareness and adoption regarding biocontrol agents against black beetle. In order to overcome this lacuna, areawide farmer participatory community based initiative has been taken up by Central Plantation Crops Research Institute, Regional Station, Kayamkulam.